The knowledge advantage: Revolutionizing tax compliance in the MSME sector - Wijaya, Suparna; Nurhastuti, Selvina; Hanifah, Dhiya; Ramadhan, Raihan; Chalista, Amellisa Devana; Luthfianti, Nabila (WIM Solusi Prima, 2025)
This study aims to examine how tax knowledge influences tax compliance levels in the MSME sector. The method used is a systematic literature review applying the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach, which includes the collection and analysis of various academic sources, journals, and related articles published between 2019-2024. From 43 identified articles, 25 articles met the inclusion criteria for in-depth analysis. The analysis results show that increased tax knowledge is positively related to increased tax compliance among MSME actors. This relationship is mediated by factors such as attitudes toward taxation, perceptions of tax fairness, and tax awareness. The main obstacles faced in strengthening tax knowledge in the MSME sector include the complexity of tax regulations, lack of education and training, and limited resources. This article suggests strategies to improve tax knowledge in the MSME sector, including simplification of tax regulations, development of continuous education programs tailored to MSME characteristics, and utilization of digital technology to expand access to tax information.